Limits of interference with the intimacy of the man. Part II - Wardak, Zbigniew (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
In the paper chosen tied problems were brought up from border of interference in the intimacy of the man, associated with the penalization of some sexual behaviors, as well as with the right to information about the genetic origin, with post-penal isolation and with the rehabilitation of perpetrators of sex offences, and legal regulation of prophylactic vaccinations.